ENHANCING CRITICAL THINKING THROUGH ASSESSMENT - Ruziev Khusniddin Bakhritdinovich (PEDAGOGS, 2024)
Abstract: This article deal with enhancing critical thinking through assessmentin English language teaching. There are many different methods to discuss and analyze.